2022
DOI: 10.3390/ijms23073533
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Inactivation of Free Fatty Acid Receptor 3 Impedes Behavioral Deficits and Pathological Hallmarks in the APPswe Alzheimer’s Disease Mouse Model

Abstract: The free fatty acid FFA3 receptor (FFA3R) belongs to the superfamily of G-protein-coupled receptors (GPCRs). In the intestine and adipose tissue, it is involved in the regulation of energy metabolism, but its function in the brain is unknown. We aimed, first, to investigate the expression of the receptor in the hippocampus of Alzheimer disease (AD) patients at different stages of the disease and, second, to assess whether genetic inactivation of the Ffar3 gene could affect the phenotypic features of the APPswe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…A recent study has already demonstrated that genetic inactivation of FFAR3 reverses the cognitive impairment showed by Tg2576 mice [ 51 ]. However, that study tested the mice at the age of 12 months, i.e., the age when the characteristic cognitive impairment present in Tg2576 begins to be manifested.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study has already demonstrated that genetic inactivation of FFAR3 reverses the cognitive impairment showed by Tg2576 mice [ 51 ]. However, that study tested the mice at the age of 12 months, i.e., the age when the characteristic cognitive impairment present in Tg2576 begins to be manifested.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a previous study addressing the role of FFAR3 in AD showed that Tg-FFAR3 −/− mice showed a significant decrease in amyloid plaque burden [ 51 ]. As described in that study, cortical homogenates obtained from 12-month-old Tg-FFA3R −/− mice showed barely detectable levels of Aβ 42 measured by ELISA, as well as a completely absence of Aβ deposits assessed by immunohistochemical analysis in hippocampal and frontal cortex sections of Tg-FFA3R −/− mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations